Inequality, Opting-out and Public Education Funding - Calin Arcalean; Ioana Cosmina Schiopu (Center for Economic Studies and ifo Institute (CESifo), 2014)
We investigate the relationship between inequality and political support for public education funding in a model of endogenous fertility and school choice. Household income heterogeneity is consistent with the skewness of empirical income distributions. Inequality can drive education spending in opposite directions in poor and rich economies. A mean preserving spread increases tax rates and public school enrollment, but decreases public spending per student in low income economies, while it has opposite effects at high income levels. An increase in the average income level can also have non-monotonic effects.
Keywords: D72; H42; I21; I22; 330; education funding; inequality; political economy